Brexpiprazole in patients with schizophrenia with or without substance use disorder: an observational study - Lombardozzi, Ginevra; Trovini, Giada; Amici, Emanuela; Kotzalidis, Georgios D.; Perrini, Filippo; Giovanetti, Valeria; Di Giovanni, Alessandro; De Filippis, Sergio (Frontiers in Psychiatry, 2023)
Background Partial dopamine D2 receptor agonists are used for psychotic symptoms in adults with schizophrenia spectrum disorders. Recently, interest surged for partial dopamine D2 receptor agonists in substance use disorders (SUDs). Since it is believed that SUDs decrease the efficacy of pharmacotherapy of underlying psychiatric disorders, we tested the efficacy of the partial D2 agonist brexpiprazole in patients with schizophrenia who were either comorbid with a SUD (SUD group) or not comorbid (non-SUD) to assess treatment response and the effect of brexpiprazole on substance craving in SUD. Methods We included patients with DSM-5/DSM-5-TR schizophrenia (using SCID-5-CV) aged 18–66 years with either comorbid SUD or non-SUD to treat with brexpiprazole 4 mg/day for 6 months during February–October 2022. Patients were assessed with the Clinical Global Impressions–Severity (CGI-S) scale, the 24-item Brief Psychiatric Rating Scale (BPRS), and the Positive And Negative Syndrome Scale (PANSS) at baseline, weekly for the first 2 months and monthly for the next four. Furthermore, we assessed substance craving in SUD with a visual analog scale for craving (VAScrav) at the same timepoints. Results The total sample was 86 (85 analysable) 18- to 64-year-old (mean 39.32 ± 14.09) patients with schizophrenia [51 men (59.3%) and 35 women (40.7%)], of whom 48 SUD (55.8%) (37 men and 11 women) and 38 non-SUD (44.2%) (14 men and 24 women). No serious or persistent adverse events developed over the study period, but one patient dropped out for subjective akathisia. Results indicated the main effects of time with improvements over the course of the study for CGI-S, BPRS, and PANSS in both SUD and non-SUD groups and the entire sample, and for VAScrav in SUD. Brexpiprazole was associated with similar significant improvements in both groups at the 6 month endpoint compared to baseline. Conclusion Treatment with brexpiprazole for 6 months improved psychotic symptoms in patients with schizophrenia, independently from whether they belonged to the SUD or the non-SUD group; hence, SUD comorbidity did not confer treatment resistance to brexpiprazole. Furthermore, in the SUD group, we observed reduced substance craving.